Institutional investors and corporate risk at the origin of the international financial crisis - Lizarzaburu, Edmundo (2023)
The 2007 financial crisis served as a stark reminder of the vulnerability in the relationship between institutions and companies, as it revealed that many companies collapsed despite government interventions. Two crucial factors that influenced the crisis’s impact on firms were the level of creditor rights protection and corporate risk management. In this study, our aim was to investigate the impact of investment funds and banks on corporate risk prior to the 2007 financial crisis. We conducted an analysis across 21 countries to examine how institutional factors determined the influence of mutual funds and banks on corporate risk, ultimately leading to critical levels of collapse and the global spread of the financial crisis to the real economy. Additionally, we explored the role of mutual funds and banks as reference shareholders. The findings of our study reveal that the process of financial deregulation preceding the 2007 financial crisis contributed to an increase in corporate risk. In other words, financial deregulation facilitated greater involvement of institutional investors in companies, thereby encouraging the adoption of excessively risky and speculative strategies that were not necessarily aligned with the long-term sustainability of firms.